The planmob and traffic municipalization as a way to ensure the right to the city (Research, Society and Development, 2023)
The theft of the right to the city from the perspective of urban mobility is a topic that deserves investigation and reflection. At first, it is necessary to contextualize the problems involved in urban mobility, which is a constitutionally guaranteed right, but often neglected by public managers. This article seeks to analyze the right to the city in this perspective of urban mobility, for which the Municipal Urban Mobility Plan and the Municipalization of Traffic stand out as the realization of the right to the city. However, before entering the potential analysis of these instruments, the context of unplanned, discontinuous and segregating urban mobility is presented. Subsequently, analyzes and reflections are presented on the legal responsibilities defined constitutionally and in the infraconstitutional legislation that incumbent on the Municipality to implement public policies for urban mobility, accessibility and road safety, which guarantee, mainly, social inclusion and quality of life for the population , based on adequate planning for urban development, making effective the constitutional right to come and go safely, as well as guaranteeing access to public spaces and services for all without distinction. Based on these assumptions, this entire article is discussed, for which the study used bibliographical research as a methodology, with analysis of specific references on urban mobility, traffic and the right to the city, in addition to special legislation on the subject.